The Wurms of Blearmouth : a Malazan tale of Bauchelain and Korbal Broach - Erikson, Steven (Erikson, Steven. Malazan book of the fallen., 2014)
"Tyranny comes in many guises, and tyrants thrive in palaces and one-room hovels, in back alleys and playgrounds. Tyrants abound on the verges of civilization, where disorder frays the rule of civil conduct and propriety surrenders to brutal imposition. Millions are made to kneel and yet more millions die horrible deaths in a welter of suffering and misery. But leave all that behind and plunge into escapist fantasy of the most irrelevant kind, and in the ragged wake of the tale told in Lees of Laughter's End, those most civil adventurers, Bauchelain and Korbal Broach, along with their suitably phlegmatic manservant, Emancipor Reese, make gentle landing upon a peaceful beach, beneath a quaint village at the foot of a majestic castle. There they make acquaintance with the soft-hearted and generous folk of Spendrugle, which lies at the mouth of the Blear River and falls under the benign rule of the Lord of Wurms in his lovely keep. Make welcome, then, to Spendrugle's memorable residents, including the man who should have stayed dead, the woman whose prayers should never have been answered, the tax collector everyone ignores, the ex-husband town militiaman who never married, the beachcomber who lives in his own beard, and the now singular lizard cat who used to be plural, and the girl who likes to pee in your lap. And of course, hovering over all, the denizen of the castle keep, Lord--Ah, but there lies this tale"--